Quantification of the temperature-dependent evolution of defect structures in a CoNi-base superalloy - Bezold, Andreas; Volz, Nicklas; Lenz, Malte; Karpstein, Nicolas; Zenk, Christopher; Spiecker, Erdmann; Göken, Mathias; Neumeier, Steffen (Acta Materialia, 2022)
Quantifying the individual contributions of specific deformation mechanisms to the total plastic strain is of primary importance to understand the underlying deformation behavior and assess the significance of the different mechanisms. However, this quantification is nearly impossible in Ni-base superalloys due to the inherent difficulties in determining the propagation distances of the respective shearing dislocations. In this study, the occurrence of stacking faults (SFs) at temperatures between 750 °C and 1000 °C in the single crystalline CoNi-base superalloy ERBOCo-4 provides an opportunity to systematically quantify the evolution of the defect structures as a function of temperature and strain after constant strain-rate compressive tests. The quantification approach revealed that deformation is still localized in the matrix at 750 °C. With increasing temperature, the main deformation mechanism changes to SF shearing, which contributes 74% of the total deformation during the initial yielding stage (∼ 0.3% plastic strain) at 900 °C. Deformation spreads significantly more homogeneously across the γ/γ’ microstructure with increasing plastic strain. Extremely high stacking fault densities and frequent fault interactions cause a pronounced work-hardening anomaly at 850 °C. Structural characterization on the atomic scale confirms the strengthening effect of SFs as barriers to partial dislocation propagation. A strong correlation between the possible diffusion length of segregating solutes and the operant shearing mechanisms reveals the significance of segregation on the occurring deformation mechanisms.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Co-base superalloy; Defect structures; High temperature deformation; Transmission electron microscopy; Yielding behavior